2013
DOI: 10.1111/tbed.12134
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Bovine Respiratory Syncytial Virus in Poland Using a Human Patient-Side Diagnostic Assay

Abstract: Bovine respiratory syncytial virus (BRSV) plays a significant role in the etiopathogenesis of the respiratory syndrome in young cattle during their first year of life. Development of rapid and accurate BRSV diagnostic tools would aid in the appropriate control of this important pathogen. The objective of this study was to characterize infections induced by BRSV by means of rapid patient-side immunomigration assays used for diagnosis of human respiratory syncytial virus (hRSV) in humans. Nasal and tracheal swab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…In the present study, the TRU RSV Ò assay detected more BRSV positive cattle, which is consistent with the results of a previous study (Urban-Chmiel et al 2013). This is due to the sensitivity of the tests and the strong nucleotide and protein sequence homology between hRSV and BRSV À more than 80% for F-antigen and 93% for N-protein (Valarcher & Taylor 2007).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the TRU RSV Ò assay detected more BRSV positive cattle, which is consistent with the results of a previous study (Urban-Chmiel et al 2013). This is due to the sensitivity of the tests and the strong nucleotide and protein sequence homology between hRSV and BRSV À more than 80% for F-antigen and 93% for N-protein (Valarcher & Taylor 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Absorbance was measured using a Bio-Rad 680 ELISA reader at a wavelength of 450 nm. BRSV detection in the nasal swabs was carried out using a rapid immunomigration assay used in diagnosing human respiratory syncytial virus (hRSV) infections in humans (TRU RSV Ò Meridian Biosciences Inc., Cincinnati, USA, Europe-Belgium) according to the manufacturer's recommendations and previously described methods (Urban-Chmiel et al 2013). …”
Section: Assays Used For Detectionmentioning
confidence: 99%
“…The serologic evidence of BRSV infections in Turkey [20,21] and other countries [22,23] has been demonstrated different studies previously. It is known that lung tissue samples containing high amount of BRSV antigens [24].…”
Section: Discussionmentioning
confidence: 90%
“…Bovine respiratory syncytial virus (BRSV) is also important virus affecting respiratory tract in cattle, especially in young calves. The serologic evidences of BRSV infections in India (Goswami et al, 2016 andHazari et al, 2002) and other countries (Urban-Chmiel et al, 2013 andSaber et al, 1996) have been demonstrated. There are many studies conducted on lung tissues in comparison to nasal swab samples from live animals.…”
Section: Detection Of Respiratory Viral Antigens In Nasal Swabs Of Bo...mentioning
confidence: 98%